Severe iron deficiency anaemia and ischaemic stroke in children. Issue 3 (27th October 2010) - Munot, P; De Vile, C; Hemingway, C; Gunny, R; Ganesan, V
Abstract : Iron deficiency anaemia (IDA) has a peak prevalence of 4–8% in children aged 1–3 years of age and is known to be associated with developmental delay, lethargy, irritability and cognitive problems. Rarely, IDA has also been reported as a risk factor for stroke in otherwise healthy children. We report a series of four young children aged 14 months to 48 months with significant IDA. Three children had venous sinus thrombosis and one had arterial ischaemic stroke, without other risk factors. We discuss the potential underlying mechanisms and review the relevant literature. This report further consolidates the evidence for a strong association between IDA and childhood stroke and highlights an easily treatable (and preventable) risk factor.